IMPROVING WAYS OF ATTRACTING FOREIGN INVESTMENTS IN THE REPUBLIC OF UZBEKISTAN (World Bulletin of Management and Law, 2022)
The article examines the processes associated with attracting foreign investments to the national economy and improving the ways of their effective use. The impact of factors on the efficiency of the country's investment activities affecting the processes of attracting and using foreign investment has been evaluated. The existing shortcomings have been identified within the framework of ways to attract and effectively use foreign investment. Scientific proposals and practical recommendations on improving the system of attracting foreign investments to the national economy have been formed